One cheeky monkey & Turtle's tall tale - Said, Aimee; Kerr, Lisa; Kerr, Lisa.; Kerr, Lisa. (Scoresby, Victoria Five Mile Press, 2014)
PICTURE STORYBOOKS. Cheeky Monkey loves to swing through the jungle - all the other animals think he's cheeky, but he's just having fun. Discover the delightful animals Cheeky Monkey encounters from the riverbed to the highest trees. Turtle is an explorer and loved retelling his wonderful adventures when he returned from his expeditions. But the sea creatures believe Turtle is telling tale tales, so when Turtle sets out on his next adventure in search of the giant golden sunfish, they all follow him. Ages 0+
"2 books and bonus height chart" -- cover.
Keywords: Monkeys -- Juvenile fiction; Turtles -- Juvenile fiction; Australian